Analysis of engineered T7 bacteriophages containing genetic sequences encoding antimicrobial peptides - Ludwig, Tobias; Volke, Daniela; Krizsan, Andor (Frontiers in Antibiotics, 2025)
Because of the global spread of multi- and pan-resistant bacteria, there is a need to identify, research, and develop new strategies to combat these pathogens. In a previous proof-of-concept study, we presented an innovative strategy by genetically modifying lytic T7 bacteriophages. We integrated DNA fragments encoding for derivatives of the antimicrobial peptide (AMP) apidaecin into the phage genome to induce the production and release of apidaecin within the T7 infection cycle, thereby also targeting phage-resistant Escherichia coli bacteria. In this follow-up study, we optimized the apidaecin encoding insert to improve the expression of the apidaecin derivative Api805 by adding the secretion signal peptide of the OmpA protein. This prevented the detrimental effects of the peptide on the producing bacterial cell after its production. The integration of two copies of the OmpA-Api805 insert into the phage genome resulted in T7Select-2xOmpA-Api805 phages, which had a partially improved activity in inhibiting phage-resistant E. coli compared to the T7Select phages without insert and with only one copy of the OmpA-Api805 insert. Additionally, we showed that the combinatorial use of the lytic bacteriophage T7Select with the highly active and lytic AMPs CRAMP (cathelicidin-related AMP) and melittin against E. coli made the lysis process of the phage and the peptides more effective and prevented the growth of potentially AMP- and phage-resistant E. coli strains. The integration of DNA sequences derived from CRAMP and melittin into the phage genome resulted in the created T7Select-(M)CRAMP and T7Select-(M)melittin phages, which showed a lysis behavior like the phage without insert and partially inhibited the growth of potentially phage-resistant E. coli strains after the phage-mediated lysis.